Analysis of Chloride Level in Rice Field Water after Fertilization in Ketapang Village by Argentometric Titration Method - Ardhi Khoirul Hakim; Ani Qomariyah (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Introduction: Agriculture plays an important role in Indonesia's international development, providing rice, corn and wheat to meet the needs of the community. Agricultural development can increase food availability and food security, as well as improve the economy and welfare of the community. One of the villages in Banyuwangi, namely Ketapang Village, is an area where most of the population works in the agricultural sector. KCl fertilizer is one type of fertilizer that is often used in rice fields to increase rice yield. Objective: This study aims to analyze chloride levels in rice field water after fertilization using KCl fertilizer, with the aim of determining the effectiveness of fertilizers that can be absorbed by plants. Methods: This research was conducted at the Chemistry Laboratory of STIKES Banyuwangi in March 2024. Mohr's Argentometric titration method was used for chloride analysis. Rice field water samples were collected from Ketapang Village. Results: The analysis showed significant variation in the percentage of chloride absorbed by plants at eight different paddy field sites after fertilization with KCl. The percentage of chloride absorbed ranged from 49.37% to 97.31%. Conclusions: The analysis showed significant variation in the percentage of chloride absorbed by plants after fertilization with KCl. Sites with a high percentage of chloride content can be considered a good indicator of fertilizer effectiveness, indicating that plants are able to absorb nutrients optimally. This has important implications in evaluating the quality of fertilization applied by farmers and can contribute to increased productivity and health of rice plants.